DOCTRINAL RULES-MAKING OF MILITARY ADMINISTRATION BODIES: LEGAL ASPECTS OF VALIDATION - Шульгін, В. (Київський національний університет імені Тараса Шевченка, 2021)
The article analyzes the legal (organizational-theoretical, comparative-applied, temporal-terminological, legitimation, validation aspects of the process of doctrinal rule-making of the military administration of the Armed Forces of Ukraine in the field of combat training and application of the Armed Forces of Ukraine and other components of the Ukrainian Defense Forces. importance on the way to the Euro-Atlantic integration of our country, for the effective operation of national joint defense forces in a special period, the preparation of units of the Armed Forces of Ukraine for joint action and interoperability with the armed forces of NATO member states. In order to form a balanced system-scientific approach to streamlining the doctrinal rule-making process of the military administration of the Armed Forces of Ukraine, an attempt was made to explore the nature, legal features of adaptation, validation and place of military publications in the national system of military administration, including doctrinal documents borrowed from member states. NATO. This is also relevant in view of the fact that the doctrine was perceived in the system of military law of Ukraine exclusively as a military-political act of the national level. It is necessary to harmonize normative-legal and doctrinal-conceptual acts of military administration of Ukraine both on the basis of their legal force in the system of normative legal acts of military legislation and taking into account their hierarchy on the basis of organizational and operational level (strategic, operational, tactical). The state of legal support of doctrinal rule-making within the framework of the Defense Forces of Ukraine and military-departmental doctrinal rule-making has been clarified. The legal essence and nature of military publications, in particular doctrines in the system of military management, their general and special concept taking into account existing problems and features of modern process of normative-legal regulation, military-departmental law enforcement, transformation of legal understanding of hierarchy of military management acts taking into account military implementation are established and substantiated. -operative doctrines, amendments to the system of national defense and military management. Proposals have been formulated in order to optimize the process of doctrinal rule-making of military administration bodies, adaptation, validation and determination of the place of military-administrative operational doctrines in the system of acts of military administration of the Armed Forces of Ukraine.

Проаналізовано правові (організаційно-теоретичні, порівняльно-прикладні, темпорально-термінологічні, легітимаційні, валідаційні) аспекти здійснення доктринальної нормотворчості органів військового управління ЗCУ у сфері бойової підготовки і застосування ЗC України та інших складових сил оборони України за призначенням, що має важливе значення на шляху до євроатлантичної інтеграції нашої держави, для ефективної діяльності національних об'єднаних сил оборони в умовах особливого періоду, підготовки підрозділів ЗСУ до спільних дій та взаємосумісності зі збройними силами держав-членів НАТО. З метою формування зваженого системно-наукового підходу на шляху упорядкування доктринального нормотворчого процесу органів військового управління ЗСУ здійснено спробу дослідити сутність, правові особливості адаптації, валідації та місце військових публікацій у національній системі актів військового управління, зокрема, доктринальних документів як запозичених у держав-членів НАТО. Зазначене актуалізовано з огляду на те, що доктрина усвідомлювалася в системі військового права України винятково як воєнно-політичний акт національного рівня. Необхідна гармонізація нормативно-правових і доктринально-концептуальних актів військового управління України як за ознаками їхньої юридичної сили в системі нормативно-правових актів військового законодавства, так і з урахуванням їхньої ієрархії за ознаками організаційно-операційного рівня (стратегічного, оперативного, тактичного) органів військового управління. З'ясовано стан правового забезпечення доктринальної нормотворчості в межах сил оборони України та військово-відомчої доктринальної нормотворчості. Встановлено та обґрунтовано правову сутність і природу військових публікацій, зокрема, доктрин у системі військового управління, їхнє загальне і спеціальне поняття з урахуванням наявних проблем та особливостей сучасного процесу нормативно-правового регулювання, військово-відомчої правореалізації, трансформації праворозуміння ієрархії актів військового управління з урахуванням імплементації військово-операційних доктрин, новелізації системи національно-оборонного та військового управління. Сформульовано пропозиції з метою оптимізації процесу доктринальної нормотворчості органів військового управління, адаптації, валідації та визначення місця військово-адміністративних операційних доктрин у системі актів військового управління ЗС України.
ДОКТРИНАЛЬНА НОРМОТВОРЧІСТЬ ОРГАНІВ ВІЙСЬКОВОГО УПРАВЛІННЯ: ПРАВОВІ АСПЕКТИ ВАЛІДАЦІЇ
Keywords: військові публікації; доктринальні документи; джерела військового права; система актів військового управління; сили оборони; військово-правові відносини; військове законодавство; доктринальні стандарти держав-членів НАТО; адаптація до стандартів НАТО; валідація; легітимація; військово-правова акультурація; military publications; doctrinal documents; sources of military law; system of military management acts; defense forces; militarylegal relations; military legislation; doctrinal standards of NATO member states; adaptation to NATO standards; validation; legitimacy; militarylegal acculturation